Peculiarities and recommendations of acute stroke treatment during the COVID-19 pandemic - Vilionskis , A.; Masiliūnas , R.; Ekkert , A.; Jatužis , D. (Neurologijos seminarai, 2020)
The global COVID-19 pandemic poses enormous challenges to healthcare systems and has a major impact on the treatment and care of stroke patients. In the article, the authors review the issues of acute stroke diagnosis, treatment, and prevention during the COVID-19 pandemic and share their own observations. Limited data on the clinical manifestations of COVID-19-associated stroke and the mechanisms of cerebrovascular injury are summarized. Practical recommendations for the organization of acute stroke care, reperfusion treatment, and secondary stroke prevention are provided. The principle is emphasized that, despite all the additional constraints imposed by the pandemic, treatment for acute stroke patients must be provided as soon as possible.